Dielectric sheet perturbation to the metallic air-filled cavity - technique of microwave non-destructive testing / Mohd Tarmizi Ali, Mohd Khairul Mohd Salleh and Prof. Madya Md Mahfudz Md Zan - Ali, Mohd Tarmizi; Mohd Salleh, Mohd Khairul; Md Zan, Md Mahfudz (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2006)
Dielectric sheet perturbation to the dominant TE111 mode resonant frequency of a circular cavity is studied and presented in this project. The dielectric sheet is placed at the middle of the air-filled cavity, introduces discontinuities and disturbs the configuration of electromagnetic fields in the cavity. For fixed dimensions of cavity and fixed thickness of the loading dielectric, the dominant resonant frequency varies quite linearly with the permittivity of the dielectric, in the range of frequency and permittivity value studied. This quasi linear relationship is plotted using Maple software and verified using 3D simulations. Two probes are used in the simulation for wave excitation into and from the cavity. The best length of probe is found to be 3 mm, giving the closest resonant frequency to the one calculated using Maple. A total of fourteen different dielectrics of permittivity varying from 1 to 12.9 are tested one by one in the simulation. The works show very close agreement between the results from Maple and the simulation. A constant difference of 0.04 GHz is found between the resonant frequencies collected during simulation and the ones from Maple. The success of this project leads than to the possibility of using the middle loaded cavity at TE111 mode as a microwave non-destructive testing of materials.